2007
DOI: 10.1016/j.ygeno.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Heritability and segregation analysis of osteosarcoma in the Scottish deerhound

Abstract: Osteosarcoma is the most common malignant bone tumor in dogs and, like its human orthologue, is characterized by aggressive local behavior and high metastatic rates. The Scottish deerhound is a breed of dog with a >15% incidence of osteosarcoma and represents an excellent spontaneously occurring large-animal model of the human disease. We modeled the transmission of the osteosarcoma phenotype in a population of over 1000 related deerhounds ascertained as part of a prospective health study. Variance component a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 23 publications
3
38
1
Order By: Relevance
“…There is an important difference between the results reported for Deerhounds in Cohort T in our study and for a large Deerhound population in an earlier study by Phillips et al [5] and the results reported for Greyhounds, Rottweilers, and Irish Wolfhounds by Karlsson et al [7]. In Deerhounds, our analysis of Cohort T and the analysis by Phillips et al suggest that osteosarcoma risk is governed largely by a single genetic variant that lies on an autosome; i.e., a single genetic variant is rather strongly associated with the osteosarcoma phenotype, and the nature of the association is cause and effect.…”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…There is an important difference between the results reported for Deerhounds in Cohort T in our study and for a large Deerhound population in an earlier study by Phillips et al [5] and the results reported for Greyhounds, Rottweilers, and Irish Wolfhounds by Karlsson et al [7]. In Deerhounds, our analysis of Cohort T and the analysis by Phillips et al suggest that osteosarcoma risk is governed largely by a single genetic variant that lies on an autosome; i.e., a single genetic variant is rather strongly associated with the osteosarcoma phenotype, and the nature of the association is cause and effect.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, our analysis strongly suggests that osteosarcoma risk in Cohort T was governed largely by a single dominant risk factor with high penetrance, as has been reported previously for Deerhounds [5]. …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations